2005
DOI: 10.1038/modpathol.3800461
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human 8-oxoguanine DNA glycosylase (hOGG1) in follicular lymphoma

Abstract: The human homologue of the yeast DNA repair enzyme 8-oxoguanine DNA glycosylase (hOGG1) repairs oxidatively damaged guanosine nucleotides in DNA. This enzyme is highly expressed in reactive germinal centers, where lymphoid cells are under oxidative stress, and has been thought to protect lymphocytes from mutation. As a first step to investigate the role of hOGG1 in lymphomagenesis, we evaluated hOGG1 expression in follicular lymphoma. Immunohistochemistry was performed on formalin-fixed paraffin-embedded tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Polymorphisms in two DNA repair genes, XRCC1 and HOGG1, have been reported to increase the risk of both lung cancer and NPC [26,27]. Myeloid leukemia has also been linked to mutations in XRCC1 [28], whereas absent/minimal HOGG1 expression occurs in the majority of follicular lymphomas [29]. Defects in those and other DNA repair genes may then partly explain the association between early-onset NPC and lung cancer, myeloid leukemia, and NHL.…”
Section: Shared Genetic Factor Hypothesismentioning
confidence: 97%
“…Polymorphisms in two DNA repair genes, XRCC1 and HOGG1, have been reported to increase the risk of both lung cancer and NPC [26,27]. Myeloid leukemia has also been linked to mutations in XRCC1 [28], whereas absent/minimal HOGG1 expression occurs in the majority of follicular lymphomas [29]. Defects in those and other DNA repair genes may then partly explain the association between early-onset NPC and lung cancer, myeloid leukemia, and NHL.…”
Section: Shared Genetic Factor Hypothesismentioning
confidence: 97%
“…Human 8‐oxoguanine‐DNA glycosylase 1 (hOGG1) is the main enzyme that excises 8‐oxo‐dG from damaged DNA via the base‐excision repair pathway [9]. It was suggested that cells under oxidative stress may require increased expression of hOGG1 to protect them from oxidative damage‐induced mutations [10].…”
Section: Introductionmentioning
confidence: 99%
“…The research on patients with lung cancer showed that low expression and repair function of hOGG1 could increase the risk for lung cancer [22] . The studies on lymphoma, astrocytoma and esophageal carcinoma also found that the expression of hOGG1 was decreased [23][24][25] . The recent research on lung cancer demonstrated that there was no significant difference in the expression of hOGG1 between cancer tissues and tumor-adjacent tissues, while the expression of hMYHα was increased significantly in tumor-adjacent tissues compared with cancer tissues [26] .…”
Section: Discussionmentioning
confidence: 99%